Dating of snow avalanches by means of wound-induced vessel anomalies in sub-arctic Betula pubescens - Arbellay, Estelle; Stoffel, Markus; Decaulne, Armelle (Boreas, 2013)
Dendrogeomorphic research has long relied on scarred trees to reconstruct the frequency of mass-movement processes. Injuries have mostly been dated macroscopically by counting the tree rings formed after wounding. Tree-ring anatomical anomalies induced by cambial injury, in contrast, have only recently been recognized as proxy records of past events. We investigated 12 sub-arctic downy birch (Betula pubescens Ehrh.) trees scarred by snow avalanches in Norway and Iceland. Earlywood vessel lumina were measured for each tree in the xylem tissue bordering the scars. Seven successive rings were examined, namely two control rings laid down prior to wounding and five rings in the wound xylem. We provide evidence that snow-avalanche-induced wounding resulted in atypically narrow earlywood vessels over at least two years. Our data demonstrate that wound-associated vessel anomalies represent tangible markers of mass-movement processes, and as such make a viable tool for reconstructing past events. Similar dendrogeomorphic studies based on tree-ring anatomy can be readily conducted with other mass-movement processes, as well as with other broad-leaved tree species. Ultimately, this new approach will foster increment coring over more invasive sampling techniques.